Quinine effects on normal spontaneous activity and on acetyl choline–induced contractures of rabbit ileal smooth muscle - Saad, Khalid. H. M. (Al-Mukhtar Journal of Sciences, 1999)
The aim of this study is to know the effect of quinine on rhythmic contractions of rabbit ileal smooth muscle and on the contractures induced by acetyl chorine. In low concentrations (0.05–0.2 mM) quinine caused gradual decline of spontaneous activity and filially abolished it completely. Moderate and high concentration (0.5–5 mM) of quinine brought about rapid relaxation, but did not effect the basic tension. The moderate concentration of quinine relaxed the muscle, which was induced to contracture by Acetyl choline. When the muscles bathed in Ca–Free solution lost their normal spontaneous contraction and normal calcium returned to the media in the presence of moderate concentrations of quinine failed to return to normal activity. These results may suggest that quinine may exert its relaxatory effect by blocking the inward calcium movement from the extra cellular medium which believed to be the trigger for smooth muscle normal contractions since this smooth muscle lack well developed sarcoplasmic reticulum